PENINGKATAN LITERASI DAN NUMERASI SISWA DENGAN BIMBINGAN BELAJAR DI SD NEGERI 173659 LUMBAN LOBU - Elza Leyli Lisnora Saragih; Kartini Sihombing; Adelina Artauli Sinaga; Lamtiur Verawaty Simbolon; Morianus Gowasa; Puspa Realita Gulo; Sri Sulastri Lumban Tobing (Jurnal Abdimas Bina Bangsa, 2023)
HKBP Nommensen University Medan sends students to do community service by helping schools according to existing needs. The schools that are partners in this PkM are Elementary Schools, namely SD Negeri 173659 Lumban Lobu. This activity aims to provide tutoring to help improve literacy and numeracy of students at SD Negeri 173659 Lumban Lobu. This activity is carried out every Monday-Thursday outside of school hours. The results of this PKM activity showed an increase in students' abilities in literacy and numeracy